Adipocytes promote malignant growth of breast tumours with monocarboxylate transporter 2 expression via β-hydroxybutyrate - Chun-Kai Huang (Nature Portfolio, 2017)
Invasion of the adipose tissue correlates with poor prognosis in breast cancer. Here, the authors show that mammary gland adipocytes promote malignancy via β-hydroxybutyrate, which acts on cancer cells through the monocarboxylate transporter MCT2 resulting in tumour-promoting epigenetic modifications.